The Effect of Compensation and Islamic Corporate Governance on Fraud Prevention with Islamic Organizational Culture as A Moderating Variable - Yusuf Faisal; Lupita Putri Yanti; Egi Gumala Sari (JESI (Jurnal Ekonomi Syariah Indonesia), 2025)
Introduction : This study aims to obtain empirical evidence regarding the influence of compensation and Islamic Corporate Governance on fraud prevention, with Islamic Organizational Culture as a moderating variable. It focuses on Islamic values in corporate governance and organizational culture and represents a novel approach to connecting these elements in the context of fraud prevention within Islamic financial institutions. Theoretically, this research enriches academic literature by presenting a comprehensive model that integrates compensation, Islamic Corporate Governance, and fraud prevention.Methodhology : This research uses a quantitative approach. Data were collected through questionnaires distributed to staff in Islamic Financial Institutions. Out of 200 distributed questionnaires, 112 valid responses were obtained from three regions. Data analysis was carried out using PLS SEM Version 3.0.Result : The findings indicate that compensation has a positive and significant effect on fraud prevention, while Islamic Corporate Governance does not. Islamic Organizational Culture moderates the relationship between compensation and fraud prevention but does not moderate the relationship between Islamic Corporate Governance and fraud prevention.Conclusion : The study highlights the importance of compensation structures aligned with Islamic values in preventing fraud within Islamic financial institutions. From a managerial perspective, fair compensation, strong ethical culture, and effective supervision are essential to enhance employee integrity and reduce fraud. From a policy perspective, regulatory frameworks are needed to support performance-based compensation and promote Islamic values in the workplace, including the provision of worship facilities, to foster a high-integrity organizational environment.